a Penerapan UU Harmonisasi Peraturan Perpajakan : Kebijakan Kenaikan Tarif PPN Hanya 1%, Tapi “Berisiko Tinggi” - Noor Safrina; Akhmad Soehartono; Aura Asrina Savitri (Indonesian Journal of Applied Accounting and Finance, 2022)
Taxes are the backbone of the nation. Nearly 80% of state revenues come from tax revenues. The foundation of the tax system needs continuous improvement. Efforts for continuous improvement in the taxation system both in terms of administration and policy continue to be made by adjusting the dynamics and the economic situation. The Law on Harmonization of Tax Regulations (UU HPP) is an important part of tax reform to build a foundation for fair, healthy, effective and accountable taxation, in the medium and long term. VAT rate adjustment is an effort to optimize tax revenue to increase the tax ratio in order to achieve a strong tax foundation. The increase in Value Added Tax (VAT) rates has received various responses, pros and cons among the public. Tires Thus, the formulation of the problem that can be presented in this scientific paper is what actually underlies this policy of increasing VAT rates and what is the impact? The purpose of this scientific paper is to find out and analyze the basis for government policy to increase the VAT rate to 11% amid the current economic recovery in Indonesia (2022) and the impact it will have on society. The results of the literature study from this scientific paper are that not all people can accept the tax increase, but the government has determined that the country's economy is stable by increasing the 11% VAT rate in 2022. The tax increase will continue in stages to improve economic stability and state financial recovery.